Assessing the effectiveness of social and political innovations in the development of interaction between the authorities and the population during COVID-19: The implication of open innovation - Elena Kranzeeva; Evgeny Golovatsky; Anna Orlova; Natalia Nyatina; Anna Burmakina (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
Open innovations combine the interaction of the authorities and the population in regions of Russia. Social and political interaction of Russian network users demonstrates new open forms of political participation, mobilization practices (initiative appeals, petitions), the use of expert systems data, and remote access technologies. The increasing number of initiatives and the growth of online communities involved in the discussion and adjustment of the results of innovation activities require the use of a big data format. The demand for open innovation based on the principles of transparency of social and political interactions is being updated during COVID-19. This study aims to assess the effectiveness of open innovations in social and political interactions during COVID-19. The innovative practices of communication between the population and authorities were studied using DataMining tools based on digital platforms: "Russian Public Initiative", "Change.org" and "GoogleTrends". Users' social graphs represent the visualization in terms of thematic and territorial groupings. The results obtained allow for a conclusion about the dependence of the regional innovation activities on the openness of their communications and their location relative to authoritative and other types of resources. The physical location of the region (center-border region-periphery) and dependence on implementation at the federal, regional or municipal levels are circumstances influencing the effectiveness of social and political innovations.
Keywords: 650; open innovation; COVID-19; innovation index; authorities; population; social innovations; government policy; large amounts of data; modeling and analysis